Efektivitas Pemanfaatan Dana Desa dalam Menunjang Pembangunan Infrastruktur di Desa Karangsalam Lor Kecamatan Baturraden, Kabupaten Banyumas - Diyanti, Balkis Dirma; Alfarisy, M. Farid; Bambang, Bambang; Apriyani, Lita (Lingka Ekonomika, 2022)
The purpose of this study is to analyze the effectiveness of the use of village funds and find out how the community views the use of village funds in terms of infrastructure development in Karangsalam Lor Village. The number of samples in this study were 88 people from Karangsalam Lor Village, Baturaden District, Banyumas Regency. Data collection techniques are interviews using a Likert scale model questionnaire. The results of this study indicate that the management and utilization of village funds in infrastructure development carried out by the Karangsalam Lor Village Government is very effective both at the level of education, health, physical infrastructure such as roads, bridges and is used for the construction of inappropriate houses and the improvement of new tourist destinations. The implication of this research is to find out how effective the use of village funds is in terms of infrastructure development in Karangsalam Lor Village, and to find out how the community's perception of the use of village funds in terms of infrastructure development in Karangsalam Lor Village. For village heads and village officials to better understand what the goals of the central government are so that development can be in accordance with what is expected and run effectively and efficiently. the community is expected to be able to participate in maintaining and caring for the development results of the village government and support what is the village government program and actively participate in the Musrenbangdes and supervision of its management.